2008
DOI: 10.1089/end.2007.0376
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus Standard Laparoscopic Partial/Wedge Nephrectomy: A Comparison of Intraoperative and Perioperative Results from a Single Institution

Abstract: Introducing a robotic interface for laparoscopic partial/wedge resection allowed a fellowship-trained urologic oncologist with limited reconstructive laparoscopic experience to achieve results comparable to those for laparoscopic partial/wedge resection performed by experienced laparoscopic surgeons. In this regard, the learning curve appears truncated, similar to that with robot-assisted laparoscopic prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(74 citation statements)
references
References 11 publications
6
64
0
4
Order By: Relevance
“…Features of the robotic arm include a tremor filtering system, motion scaling, dexterity, and ambidexterity, and these enable surgeons to access deep and narrow spaces for complete cervical lymph node dissection and are likely to increase the facility of preserving the parathyroid gland and RLN. [6][7][8][9][10]19,20 Robotic thyroidectomy using a gasless transaxillary approach was first performed in 2007 by Chung and coworkers. 7 However, robotic thyroidectomy with cervical lymph node dissection is not widely used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Features of the robotic arm include a tremor filtering system, motion scaling, dexterity, and ambidexterity, and these enable surgeons to access deep and narrow spaces for complete cervical lymph node dissection and are likely to increase the facility of preserving the parathyroid gland and RLN. [6][7][8][9][10]19,20 Robotic thyroidectomy using a gasless transaxillary approach was first performed in 2007 by Chung and coworkers. 7 However, robotic thyroidectomy with cervical lymph node dissection is not widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential advantage of a robot approach performing CCND is that surgeons can simultaneously manipulate 3-arm system. [6][7][8]19,20 In conventional endoscopic procedure, the surgeon can use only 2 arms during lymph node dissection, and it took more effort and time to perform accurate lymph node dissection. Therefore, these 3-arm systems combined with 3-D magnified view of robot provide surgeon the ability to perceive depth and space in the surgical field more accurately and facilitate the ability to perform precise and meticulous dissection during CCND.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These amenities may allow the surgeon to replicate established maneuvers employed during OPN, allow for extirpation of complex, centrally located tumors, and reconstruction of the pelvicaliceal system. The feasibility and safety of RAPN has been demonstrated in several small, single institution studies (Gettman et al 2004;Phillips et al 2005;Caruso et al 2006;Kaul et al 2007;Aron et al 2008;Deane et al 2008;Benway et al 2009;Ho et al 2009;Michli and Parra 2009;Benway et al 2010). Recent studies have demonstrated the feasibility of RAPN for larger, deeper tumors that are hilar in their location as well as for multiple tumors in the hereditary renal cancer population (Rogers et al 2008;Boris et al 2009;Gupta et al 2011).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…In fact, one recent study has even shown a shorter learning curve for robot-assisted partial nephrectomy, thus leading to increased permeation of this surgical modality. 27 …”
Section: Robot-assisted Partial Nephrectomymentioning
confidence: 99%